1977
DOI: 10.2527/jas1977.453543x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Apple Pomace with Nonprotein Nitrogen for Gestating Beef Cows. IV. Pesticide Accumulation in Cows

Abstract: Samples of fresh apple pomace were collected from 14 loads of apple pomace as delivered from the processing plant in October 1968 and from stored apple pomace that had been obtained in October 1967 and fed during a feeding trial from mid-November 1967 through April 1968. All samples were analyzed for dicofol (kelthane), tetradifon (tedion), DDT, DDD and DDE. For the pesticide residues in fresh apple pomace, the difference between the low and high load means was greater than 10-fold and these differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…recent data have shown a consistent pattern of residue concentrations across several fat deposits as shown for dieldrin in figure 7 (Rumsey and Bond, 1974). This same pattern among tissues was generally consistent with DDT at high and low residue loads (Rumsey et al, 1967;Rumsey et al, 1977a). An understanding of this phenomenon may suggest a way to control or regulate lipophilic residues.…”
Section: Residue Curvesupporting
confidence: 69%
“…recent data have shown a consistent pattern of residue concentrations across several fat deposits as shown for dieldrin in figure 7 (Rumsey and Bond, 1974). This same pattern among tissues was generally consistent with DDT at high and low residue loads (Rumsey et al, 1967;Rumsey et al, 1977a). An understanding of this phenomenon may suggest a way to control or regulate lipophilic residues.…”
Section: Residue Curvesupporting
confidence: 69%
“…This might be related to the increased Mn requirements under high calcium or potassium diets (14 ). Apple pomace has not been recommended as a ruminant feedstuff in the USA because of high pesticide residues (24 ). Its use in New Zealand as an animal foodstuff seems to be recent and is related to the increased processing of apples for beverages.…”
Section: Discussionmentioning
confidence: 98%
“…Bovard et al (1977) have reported on the skeletal abnormalities of the calves born from cows fed NPN supplements and apple pomace. Rumsey et al (1977) have reported on the pesticide accumulation in the cows fed these diets.…”
Section: Discussionmentioning
confidence: 99%